Implementation of Maqashid Syariah to the Customer Service Unit in Providing Services to Customers at PT. Bank Sumut Syariah KCP Lubuk Pakam - Zaini Abdillah Siregar; Nur Santri Yanti (Penerbit Jurnal Indonesia, 2022)
The role of customer service is indispensable as the first liaison between customers and Islamic banking. Customer Service activities in sharia banking are based on sharia principles and in accordance with sharia objectives, namely maqashid sharia. The implementation of maqashid sharia under study is to see the implementation of maqashid sharia in services to customers carried out by Customer Service. The purpose of this research is to see every activity of Customer Service in providing services to customers. The method used is qualitative research, with descriptive data analysis method. The discussion of the research is to see 5 (five) aspects of maqashid sharia obtained by interviewing Customer Service. Maqashid sharia in the realm of Customer Service, emphasizes the extent to which the implementation of the five concepts of maqashid sharia in terms of maintaining religion, guarding souls, guarding reason, protecting offspring, and protecting assets at PT. Bank Sumut Syariah KCP Lubuk Pakam. The results of the research on the implementation of maqashid sharia in the Customer Service unit were carried out in accordance with maqashid sharia.